Cost-benefit analysis of public cloud versus in-house computing - Abdi Abdulle, Abdikarim; Ali, Abdifatah Farah; Haji Abdullah, Rusli (Seventh Sense Research Group, 2022)
The transformation of the Information Technology world has been evolving exponentially in the last couple of years. The technology gives many choices, enabling businesses, educational institutes, health, and industries to have the computational power and monetary performance, which is highly affected by their routine work. Many business companies are trying to move to the cloud for computing and storing their information on the system and decide which is cost-effective for in-house computing and Public Cloud. The objective of this study is to compare and calculate capital expenditure (Capex) and operational expenditure (Opex), which focuses on cost-benefit analysis of public cloud versus in-house computing, and develop a decision tree diagram that shows the benefits of cost-effectiveness, privacy, and data confidentiality, service level agreement, and real-time application. According to the Cost, the study shows that the public cloud is less expensive than in-house computing; most of the cost incurred by in-house computing is a power consumption cost. However, in-house computing is effective on the benefits side